Single-sized metasurface for simultaneous pseudo-color nanoprinting and holographic image display - Li, Jiaxin; Zhou, Zhou; Li, Zile; Zheng, Guoxing (Frontiers in Nanotechnology, 2022)
Metasurfaces provide a novel platform for multifunctional devices due to their incomparable competence for the manipulation of different optical properties. Recently, many works have emerged to merge distinct functions into a single metasurface, which effectively increase the information density and capacity of meta-devices. In this work, combining the dual-wavelength polarizer and the orientation degeneracy of the Malus law, we further exploit the design degree of freedom of the metasurface, and realize color control and phase manipulation simultaneously with single-sized nanostructures. We experimentally demonstrate our concept by integrating the function of pseudo-color nanoprinting and holographic image display together. Our research can effectively improve the functionalities of metasurface and promote advanced research of multimode displays, information encryption, optical multiplexing, and many other related fields.